Fulfilling information needs of new Muslims: trends and challenges - Abdul Rahman, Habsah; Othman, Roslina (2011)
The wave of Islamic awareness is sweeping across nations and continents even though there is much sabotage and propaganda against the Faith. Muslims are now excited with this development and have responded with a corresponding rate of information provision, bringing about a proliferation of Islamic information. These information sources produced sometimes may or may not be appropriate for consumption if not addressed according to specific needs.